Work-Life Balance, Work Engagement and Employee Performance: An Examining the Mediating Role of Job Satisfaction - Iswanda Imawan; Muhammad Taufik Lesmana; Muslih Muslih (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose -This research examines the effect of work-life balance and work engagement on employee performance through job satisfaction at the Belawan Branch of the Multi Terminal Sub Pelindo.Method -The approach used in this research is an associative quantitative approach. This study's population was all Pelindo Multi Terminal Sub Belawan Branch employees. The sample in this study used a saturated sample method totaling 98 employees at the Belawan Branch of the Pelindo Multi Terminal Sub Branch. Data collection techniques in this research used interviews and questionnaires. The data analysis technique uses a quantitative approach using SEM-PLS.Findings -The results of this research show that work-life balance, work engagement, and job satisfaction have a positive and significant effect on employee performance, work-life balance, and work engagement have a positive and significant effect on job satisfaction, work-life balance, and work engagement have a positive and significant effect on employee performance through Job satisfaction at Sub Pelindo Multi Terminal Belawan Branch.Originality/Novelty - Combining two main concepts, namely work-life balance and work engagement, in one research model can provide a deeper understanding of the complexity of the relationship between the variables of work-life balance, work engagement, job satisfaction, and employee performance.Implications -This research has shown that job satisfaction mediates the influence of work-life balance and work engagement on employee performance. Recommendations for further research include analyzing or using the job satisfaction variable as an independent variable, not a mediating variable.